HUBUNGAN DUKUNGAN SOSIAL DAN STRES KERJA DENGAN BURNOUT PADA PERAWAT IGD DAN ICU RSUD DR. HASRI AINUN HABIBIE - Ntobuo, Fendi; Syamsuddin, Lenny; Rahim, Putri (Elsia: Jurnal Psikologi Manusia, 2024)
The purpose of this study is to investigate the connection between burnout from work stress and social support. The nurses at the ICU and emergency room at Dr. Hasri Ainun Habibie. This study takes a quantitative approach and employs a correlational study design. Total sampling was used to collect the samples. There were 40 responders, 24 of whom were ER nurses and 16 of whom were ICU nurses. This study used the multiple correlation approach. According to the study's findings, there is a significant negative relationship between social support and burnout (correlation coefficient value = -73.1%), a positive and significant relationship between job stress and burnout (correlation coefficient value = 41.4%), and a relationship between social support and job stress with burnout (correlation coefficient value = 46.4%). The ER and ICU nurses at Dr. Hasri Ainun Habibie report a jointly significant association between social support and job stress burnout, as indicated by the coefficient of determination value (R square) of 53.5%.